EFEKTIVITAS MODEL MAHIR DALAM MENINGKATKAN AKTIVITAS, KETERAMPILAN BERPIKIR KRITIS DAN HASIL BELAJAR SISWA SEKOLAH DASAR - Hidayani; Cinantya, Celia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The problem in this study is the low activity, critical thinking skills, and student learning outcomes in the subject of science, which is caused by less meaningful learning, one-way, and a lack of activities to sharpen critical thinking. The solution applied is the MAHIR learning model. The purpose of this study is to describe teacher activities and analyze student activities, critical thinking skills, and learning outcomes. The study used a qualitative approach with Classroom Action Research (CAR) during three meetings in grade V SDN Pangeran 2 in the 2024/2025 academic year, with nine students as subjects. Data were collected through observation and written tests, then analyzed descriptively using cross tables. The results showed that teacher activity became